LOW PROTEIN DIET DURING PERIPUBERTAL PHASE PROGRAMS TO CARDIOVASCULAR DYSFUNCTION IN ADULT RATS (Arquivos do Mudi, 2023)
Perinatal malnutrition has a devastation effect later in life. This study evaluated whetherprotein restriction in adolescent rats programs hypertension regarding cardiac dysfunction.CEUA approved the experimental protocol under nº 3353060421. 30-day-old Wistar male ratswere fed a low protein diet (4%) for the next thirty days and subsequently fed a 20.5% normalprotein diet for the next 60-days with normal diet (LP group). Control rats (NP group) werefed a normal protein diet throughout life. Cardiovascular system function was evaluated with120-days-old. Statistical analyses were performed with T-Student test. LP animals displayedan inferior body mass and nose-tail length (P=0.0001; P=0.01) and also rising retroperitonealfat (P=0.03). LP rats exhibited a higher in mean arterial blood pressure (p=0.05). In theechocardiogram, LP group showed an increased in the diameter (p=0.01, p=0.02),interventricular septum (p=0.040 e p=0.03) and the in posterior wall (p=0.01 e p=0.03) of theleft ventricle in diastole and systole respectively. Protein restriction in peripubertal periodleads to hypertension in adulthood, sustained by greater cardiac dysfunction.